TRIBOLOGICAL BEHAVIOR OF POLYMERIC MATERIALS FOR HYBRID MET-ALLOPOLYMER UNITS OF DRY SLIDING FRICTION. PART. 4. POLYTHETRA-FLUOROTHYLENE (FLUOROPLASTS) - Чернець, Мирон; Корнієнко, Анатолій; Руденко, Павло (Problems of Friction and Wear, 2022)
In accordance with the method of model triboexperimental studies of materials during sliding friction according to the scheme of end friction, the wear resistance of composites based on polytetrafluoroethylene PTFE-4: PTFE + 15C + 5MoS2, PTFE + 10CF + 15TiC, PTFE + 15CF, PTFE + 15CF was investigated. They are widely used in metal-polymer (MP) plain bearings operating in conditions of dry sliding friction. Their wear resistance indicators are established, based on which their wear resistance characteristics are determined, as used in computational research methods of these hybrid tribomechanical systems. Quantitative regularities of tribological behavior of the specified composites of polytetrafluoroethylene in tribocouples with steel 45 are established. The results of loading influence on change of sliding friction coefficients are resulted.